Is agricultural digitization a reality among smallholder farmers in Africa? Unpacking farmers' lived realities of engagement with digital tools and services in rural Northern Ghana - Abdulai, Abdul-Rahim; Tetteh Quarshie, Philip; Duncan, Emily; Fraser, Evan (Springer, 2023)
Background Digital technologies are promoted as transformational for smallholders in Africa through the potential to enhance access to knowledge, increase productivity and food security. Despite the anticipations for agricultural digitalization in Africa, smallholders' engagement with digitalization is empirically underexplored. Hence, we surveyed 1565 rural farmers in Northern Ghana to explore how farmers interact with digital tools and services, and the variations in their engagements.